Evolution of models to support community and policy action with science: Balancing pastoral livelihoods and wildlife conservation in savannas of East Africa - Reid, Robin S.; Nkedianye, D.; Said, Mohammed Yahya; Kaelo, D.; Neselle, M.O.; Makui, O.; Onetu, L.; Kiruswa, S.; Ole Kamuaroa, N.; Kristjanson, Patricia M.; Ogutu, J.; BurnSilver, S.B.; et al. (National Academy of Sciences, 2016)
We developed a “continual engagement” model to better integrate knowledge from policy makers, communities, and researchers with the goal of promoting more effective action to balance poverty alleviation and wildlife conservation in 4 pastoral ecosystems of East Africa. The model involved the creation of a core boundary-spanning team, including community facilitators, a policy facilitator, and transdisciplinary researchers, responsible for linking with a wide range of actors from local to global scales. Collaborative researcher–facilitator community teams integrated local and scientific knowledge to help communities and policy makers improve herd quality and health, expand biodiversity payment schemes, develop land-use plans, and fully engage together in pastoral and wildlife policy development. This model focused on the creation of hybrid scientific–local knowledge highly relevant to community and policy maker needs. The facilitation team learned to be more effective by focusing on noncontroversial livelihood issues before addressing more difficult wildlife issues, using strategic and periodic engagement with most partners instead of continual engagement, and reducing costs by providing new scientific information only when deemed essential. We conclude by examining the role of facilitation in redressing asymmetries in power in researcher–community–policy maker teams, the role of individual values and character in establishing trust, and how to sustain knowledge-action links when project funding ends.